Environmental Impact Assessment of Geothermal Power Plant: Analysis Using Life Cycle Assessment (LCA) and Analytical Hierarchy Process (AHP) Methods - Altelah Anisa Valmay; Udisubakti Ciptomulyono (International Journal Labs, 2026)
This study aims to identify the environmental impacts arising from the electricity generation process at PT. X and to determine alternative mitigation scenarios that can be applied to reduce these environmental impacts. Using the Life Cycle Assessment (LCA) approach, the study successfully identified the Cooling Tower as the main hotspot in the generation process, with emissions such as CO?, H?S, NH?, and NO? contributing to global warming potential, acidification potential, eutrophication potential, and human toxicity. Based on the analysis using Analytical Hierarchy Process (AHP), the most effective mitigation alternative to reduce environmental impacts is the use of High Performance Lubricant (HPL) for the Fan Cooling Tower (FCT) system. The use of HPL received the highest priority, with a weight of 46.9% of the total decision, as it can reduce friction and heat, leading to improved energy efficiency and reduced motor power consumption. This research contributes to the development of mitigation strategies that can be applied to achieve a more sustainable, efficient, and environmentally friendly geothermal power plant, while also supporting Indonesia's energy transition.